DEVICE FOR INCREASED WATER TEMPERATURE IN FISH CARE CONTAINERS AND RESERVOIRS (Journal of Universal Science Research, 2024)
The device contains a heat storage chamber, covered with selective glass and consisting of a set of thin-walled copper tubes, between which are filled with heat storage material, which is sodium dihydrogen phosphate crystal hydrate. Radiators in the form of metal plates are located along the entire outer surface of the heat pipes, and spiral swirlers are located inside.